2021
DOI: 10.1002/mdc3.13307
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Evaluation in Multiple System Atrophy: A Retrospective Cohort Study

Abstract: BackgroundBackground: Urological dysfunction in patients with multiple system atrophy (MSA) is one of the main manifestations of autonomic failure. Urodynamic examination is clinically relevant since underlying pathophysiology of lower urinary tract (LUT) dysfunction can be variable. Objective Objective: Evaluation of the pathophysiology of urological symptoms and exploration of differences in urodynamic patterns of LUT dysfunction between MSA-P and MSA-C. Methods Methods: Retrospective study of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(155 reference statements)
0
4
1
Order By: Relevance
“…Compared to previous studies [ 10 , 12 , 37 , 55 ], we did not observe an association between sex and urinary incontinence or catheterization. In the general population, perineal laxity and multiparity are well-known factors that contribute to urinary incontinence in women, while prostate hypertrophy may cause urinary retention in men.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Compared to previous studies [ 10 , 12 , 37 , 55 ], we did not observe an association between sex and urinary incontinence or catheterization. In the general population, perineal laxity and multiparity are well-known factors that contribute to urinary incontinence in women, while prostate hypertrophy may cause urinary retention in men.…”
Section: Discussioncontrasting
confidence: 99%
“…The literature on sex-related differences in the clinical presentation of MSA suggested that compared to men, women more frequently have a motor symptomatic onset and a better response to L-dopa, but overall develop greater motor disability over time and more frequently suffer from pain, depression, anxiety, sarcopenia, frailty, early falls, fractures, worse cognitive performance, and lower health-related quality of life [ 10 , 11 , 22 , 25 , 31 , 48 , 50 , 51 , 59 ]. By contrast, men were more frequently reported to have an autonomic symptomatic onset and to suffer from more widespread and severe autonomic failure, except for urinary urge incontinence and constipation, which were more common in women [ 10 , 12 , 20 , 34 , 36 , 37 , 41 , 51 , 55 , 60 , 61 ]. Higher supine BP levels as well as greater orthostatic BP falls were both associated with increased mortality in men with MSA [ 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of DU has been found to be increased to 62.1% in patients with MSA and 71.4% in patients with post-void residual (PVR) > 100 mL. Additionally, the strength of the detrusor in MSA-P has been found to be weaker than that of MSA-C (P det @Q max 26.2 vs. 34.4 cmH 2 O, p = 0.04) [25]. A recent systematic review found that 12% of patients with multiple sclerosis (MS) experience an atonic bladder [26].…”
Section: Neurogenicmentioning
confidence: 98%
“…The only tests needed to fulfil core clinical criteria are a postvoid bladder residual volume and a lying and standing blood pressure. However, if uncertainty remains, other investigations can help to prove autonomic involvement, for example formal urodynamics showing detrusor sphincter dyssynergia 15 or external anal sphincter electromyography showing chronic reinnervation changes in Onuf’s nucleus (however, this finding is not specific to MSA, and occurs in long-standing Parkinson’s disease, progressive supranuclear palsy and after pelvic surgery). 16 …”
Section: Diagnosing Msamentioning
confidence: 99%